Chroma a Filipino LGBTQ+ resources and information center - De Guzman, Rhon Michael B.; Perion, Sharon (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
In this current social climate, LGBTQ+ people continue to face different forms of discrimination. Although Philippines might be dubbed as a "gay-friendly" country, many of the Filipino LGBTQ+ would disagree on this and would rather say Filipinos are tolerating rather than accepting. With this, the thesis project design aims to create a facility that would allow anyone, regardless of their sex or gender or any status in life, to access the development and be educated of what the ideals and the knowledge about being part od the LGBTQ+ community through symposia, conferences, art forms, and even films or plays. The design takes into consideration the needs that both the heterosexuals and the LGBTQ+ people needs. From said issues as well, goals are established and are anchored upon safety and security, people-oriented, transparency, and LGBT imagery. As Such, the overall outcome of the design shows that to be able to attract people and make it "LGBT" is to make it friendly and accessible for everyone; and services should be related to what could help individuals and groups, part or not part of the LGBTQ+ community be a well-educated citizen.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: LGBTQ+.; LGBTQ+ Information Center -- Design